2020
DOI: 10.5811/westjem.2020.3.45932
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Community Organization Perspectives on Accessing Social Resources from the Emergency Department: A Qualitative Study

Abstract: Introduction: Social risks adversely affect health and are associated with increased healthcare utilization and costs. Emergency department (ED) patients have high rates of social risk; however, little is known about best practices for ED-based screening or linkage to community resources. We examined the perspectives of patients and community organizations regarding social risk screening and linkage from the ED. Methods: Qualitative interviews were conducted with a purposive sample of ED patients and local com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(55 citation statements)
references
References 16 publications
1
54
0
Order By: Relevance
“…The literature surrounding screening for social needs and risk factors has largely focused on implementation processes and barriers and in the clinic or hospital environment. [16][17][18] Although the challenges and perspectives of providers have been well described, the patient experience and perceptions of discussing SDOH are not well understood. In the nationwide 2018 Consumer Perspectives on How Social Determinants Impact Clinical Experience, a report conducted by Waystar, 19 it was found that 68% of Americans identified having challenges in at least one SDOH risk category.…”
mentioning
confidence: 99%
“…The literature surrounding screening for social needs and risk factors has largely focused on implementation processes and barriers and in the clinic or hospital environment. [16][17][18] Although the challenges and perspectives of providers have been well described, the patient experience and perceptions of discussing SDOH are not well understood. In the nationwide 2018 Consumer Perspectives on How Social Determinants Impact Clinical Experience, a report conducted by Waystar, 19 it was found that 68% of Americans identified having challenges in at least one SDOH risk category.…”
mentioning
confidence: 99%
“…10 -14 Several studies have explored patient perceptions of addressing social needs in clinical settings, 10 ,12-19 related both to specific domains like intimate partner violence 20,21 and to food insecurity 12,13,17 as well as social needs screening more generally. Most participants across studies agreed that health care providers should ask patients about social needs, 10,12,13,16,18,19 though some added qualifications, including concern for privacy regarding sensitive topics. 14 Less research to date has focused on ED patients' views on social needs screening, 10,13,15,16 with very little devoted to housing issues specifically.…”
Section: Importancementioning
confidence: 99%
“…Most participants across studies agreed that health care providers should ask patients about social needs, 10,12,13,16,18,19 though some added qualifications, including concern for privacy regarding sensitive topics. 14 Less research to date has focused on ED patients' views on social needs screening, 10,13,15,16 with very little devoted to housing issues specifically. One scoping review of ED-based interventions related to social needs found that, of 135 studies, only 3% focused on housing issues.…”
Section: Importancementioning
confidence: 99%
See 2 more Smart Citations